Age- and gender-specific reference values of estimated GFR in Caucasians: The Nijmegen Biomedical Study - Wetzels, J.F.M.; Kiemeney, L.A.L.M.; Swinkels, D.W.; Willems, H.L.; Heijer, M.den (Kidney international, 2007)
The Nijmegen Biomedical Study is a population-based cross-sectional study conducted in the eastern part of the Netherlands. As part of the overall study, we provide reference values of estimated glomerular filtration rate (GFR) for this Caucasian population without expressed risk. Age-stratified, randomly selected inhabitants received a postal questionnaire on lifestyle and medical history. In a large subset of the responders, serum creatinine was measured. The GFR was then measured using the abbreviated Modification of Diet in Renal Disease (MDRD) formula. To limit possible bias, serum creatinine was calibrated against measurements performed in the original MDRD laboratory. The study cohort included 2823 male and 3274 female Caucasian persons aged 18–90 years. A reference population of apparently healthy subjects was selected by excluding persons with known hypertension, diabetes, cardiovascular- or renal diseases. This healthy study cohort included 1660 male subjects and 2072 female subjects, of which 869 of both genders were 65 years or older. The median GFR was 85 ml/min/1.73 m2 in 30–to 34-year-old men and 83 ml/min/1.73 m2 in similar aged women. In these healthy persons, GFR declined approximately 0.4 ml/min/year. Our study provides age- and gender-specific reference values of GFR in a population of Caucasian persons without identifiable risk.